After Release: A Qualitative Investigation into the Financial Lives of Previously Incarcerated Individuals. Issue 1 (2nd January 2018) - Mielitz, Katherine; Lurtz, Meghaan; Clady, Joy; Archuleta, Kristy
ABSTRACT: Research related to post release of previously incarcerated individuals has long focused on recidivism, post-incarceration employment, education, family support, and substance abuse treatment. One area that has not been well explored in postrelease inquiry is how financial knowledge and behavior shape the previously incarcerated individual as they reintegrate into society. This qualitative study explored the research question, "What are post incarcerated individuals' experiences of self-identified financial behavior change?" Content analyses were conducted with the interviews of 42 previously incarcerated individuals, discussing their financial attitudes, knowledge, and behaviors: budgeting, spending choices, and savings. The findings of this study include a presence of family influence, perceptions of financial behavior change, confusion regarding banking and credit, and a general lack of financial knowledge among respondents.